An Application of Classical Test Theory for Item Characteristic Analysis of Chemical Literacy Instruments - Ningsih, Sri Nurfadillah; Istiyono, Edi; Widihastuti (Universitas Pendidikan Ganesha, 2023)
The science literacy skills of students in Indonesia are very concerning, the cause is that students are not accustomed to working on questions based on science literacy, so it is necessary to have a standardized assessment instrument based on chemical literacy that can measure the level of achievement of scientific identification and interpret science/chemistry learning. This study aimed to describe the characteristics of chemical literacy-based assessment instrument items of reaction rate material with a classical test theory approach. The type of research is descriptive quantitative. The research subjects were 80 class XI MIPA SMA Negeri 4 Takalar students. Data were analyzed using the ITEMAN 4.3 program. Based on the results of the analysis, a reliability coefficient of 0.834 was obtained, the level of favorability of 87% of the items was in the moderate category, and 13% was in the difficult category. In the difference test, as many as 73% of the items are in the very good category, and for the distractor test, 93% of all items have shown distractors that function properly, so it can be concluded that overall the items have high reliability and good item characteristics.